2018
DOI: 10.1016/j.chroma.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salts on retention in hydrophilic interaction chromatography

Abstract: There is a widespread belief that salts promote retention of solutes in hydrophilic interaction chromatography (HILIC) by expanding the volume of the immobilized layer of water on the surface of the stationary phase. To date, all studies of this premise have had flaws or limitations that left the question open. This study explored the effects of salt type and concentration. The effect of the anion was studied with four triethylammonium salts, ranging from the kosmotropic sulfate to the chaotropic perchlorate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…In the case of temperature this phenomenon was constant for a wide temperature range [44] whereas for buffer concentration it was apparent only above certain concentration value. At lower concentration levels the retention factor decreased with increasing buffer concentration, whereas at higher concentration levels the retention factor increased with increasing buffer concentration [45] (compare Fig. 3).…”
Section: Robustnessmentioning
confidence: 83%
“…In the case of temperature this phenomenon was constant for a wide temperature range [44] whereas for buffer concentration it was apparent only above certain concentration value. At lower concentration levels the retention factor decreased with increasing buffer concentration, whereas at higher concentration levels the retention factor increased with increasing buffer concentration [45] (compare Fig. 3).…”
Section: Robustnessmentioning
confidence: 83%
“…Cytosine has been used to evaluate the performance of various polar stationary phases in HILIC [25]. Recently, Alpert demonstrated by comparing the retention of cytosine and cytidine that cytosine might have specific interactions with the Hydroxyethyl A phase [26]; however, the unusual elution pattern was not observed on Altantis HILIC silica, YMC Pack amino, TSKgel Amide-80, and ZIC-HILIC phases [25]. Uracil has two pKa values: pKa 1~9 .36 and pKa 2~1 3.49.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the acetonitrile level, previous studies have demonstrated that the salt concentration can have significant effect on the retention of the neutral compounds in HILIC [25][26][27]. We selected three stationary phases, namely, ZIC-HILIC 3, XBridge Amide, and LUNA HILIC 2 to represent different levels of retentivity based on the previous results (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Discussing the possible interactions governing retention is rather difficult due to the unknown stationary phase chemistry and the mixed-mode operation. The solvation of the analytes and their dissociation states are strongly influenced by the acetonitrile ratio in the mobile phase [37]; and the fact that besides the effective pH [38,39], the ionic strength may also have an influence [29], further complicating the picture. Instead of the pure HILIC and WAX operation conditions, their resultant determines the retention.…”
Section: Discussion Of Retention Mechanismmentioning
confidence: 99%
“…Although frequently used in ion (exchange) chromatography, salt gradients are almost entirely neglected in HILIC-based chromatography, mainly because of the lack of theoretical understanding of the retention mechanisms which still need theoretical and experimental elucidation [29][30][31]. Using salt gradients in reversed-phase chromatography is also uncommon, even for pH-gradient there are only a few reported examples [32,33].…”
Section: Chromatographic Methods Have Beenmentioning
confidence: 99%